Pengaruh Edukasi Media Video Animasi tentang Pentingnya Tablet FE untuk Pencegahan Stunting terhadap Pengetahuan Remaja Putri di SMP N 1 Wedi - Ermalia Hanifah; K.H.Endah Widhi Astuti; Lutfiana Puspita Sari (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Stunting remains a health problem with high rates, including in Klaten Regency. Prevention can begin in adolescent girls by increasing knowledge about the importance of consuming iron tablets. Animated video media is considered more effective in increasing adolescent girls' knowledge regarding stunting prevention. Objectives: To determine the effect of educational media using animated video media about the importance of iron tablets on the knowledge of adolescent girls at SMP N 1 Wedi, Klaten Regency, as an effort to prevent anemia and stunting. Methods: This study used a quantitative method. The design used was a pre-experimental approach with a one-group pretest-posttest approach. The study population was 129 eighth-grade female students at SMP N 1 Wedi, with a sample size of 40. The sampling technique used was Proportional Stratified Random Sampling. Data collection was carried out using a questionnaire. The analysis technique used was the Wilcoxon test. Results: The study showed an increase in knowledge of adolescent girls regarding the importance of iron tablets in preventing stunting before and after being provided with education through animated videos at SMP N 1 Wedi, with a p-value of 0.000 (p < 0.005). Conclusion: Education using animated videos is effective in improving the knowledge of eighth-grade adolescent girls at SMP N 1 Wedi. Keywords: Stunting, Iron Tablets, Adolescent Girls, Animated Video, Knowledge.